Reasons of Destructive Law-Enforcement Practice, Way of Solution: Questions of Implementation of Experiment of the Leading Foreign Countries of the Prevention of Transnational Organized Crime in the Criminal Legislation - ESENOV, Dastan (Journal of Advanced Research in Law and Economics, 2018)
Considering the reasons of the destructive law-enforcement practice promoting integration of national criminal communities into criminal corporations of transnational character it should be noted that they are illogical to the causes of actually organized crime as steady social phenomenon. Based on the specified opinions, criminologists note that regeneration of organized crime in transnational has also become possible thanks to social and economic contradictions between the countries which were shown in the aspiration of separate groups of persons to receive unlimited financial benefit from criminal activity, to master new sources of the criminal income, to research new opportunities of criminal business of the modern world. Thus, the concept of generation of considerable social contradictions during changes comes to the forefront as the reason of development of transnational organized crime. New social and economic realities, technological progress, crises and recessions, formation of the open markets and free trade, democratization, institutional reforms have led to emergence of new forms and types of criminal activity including transnational organized crime.